The effect of educational intervention based on self-efficacy theory on promoting adolescent oral health behaviors through mobile application: a randomized controlled trial study - Seyedeh Zahra Marashi; Alireza Hidarnia; Seyedeh Somayeh Kazemi; Ghodratollah Shakerinejad (BMC, 2024)
Abstract Background Oral health is so important for the adolescent age group that the World Health Organization has listed oral health as a lifelong prerequisite for maintaining public health; Therefore, this research was carried out with the aim of the effect of educational intervention based on self-efficacy theory on the promotion of behaviors related to oral health of adolescents through mobile application. Methods In this clinical trial, 80 adolescents aged 13-15 years from Shushtar city were selected using a random cluster sampling method and assigned to either the test or control group. The data collection tools included a standard questionnaire for measuring Oral health behavior (awareness, attitude, behavior) and a standard questionnaire for measuring self-efficacy (self-efficacy in brushing teeth, self-efficacy in using dental floss, and self-efficacy in visiting the dentist), as well as demographic characteristics. Training was provided to the test group via a mobile application for 3 weeks. During the intervention, the control group did not receive any training. Questionnaires were distributed in both groups immediately after the intervention, as well as one month and three months post-intervention, and data were collected. In accordance with research ethics, at the end of the study, the educational content was provided to the control group. Collected data were analyzed using SPSS 22 software and Mann-Whitney and Friedman non-parametric tests. Results The findings showed that the educational intervention through the mobile application was effective in improving the average scores of awareness, attitude, self-efficacy in brushing teeth, flossing, visiting the dentist, and the behavior of adolescents regarding oral health behaviors, and this statistical difference was significant compared to before the educational intervention (P < 0.05), while no change was observed in the control group (p > 0.05). Conclusion Considering that adolescents aged 13-15 years are the age of starting behavioral habits, including oral health behaviors, and on the other hand, their interest in using technology and virtual spaces is high, it is suggested that part of the education of this age group should be designed and implemented in the platform of mobile application. Clinical Trial Registration in Iran Clinical Trial Center with ID code (IRCT20200120046204N1) Date of.Registration: 2018-02-25.